A forradalom arca. Egy pesti lány nyomában . The Face of the Revolution In Search of a Girl from Budapest - Kékesi, Attila (Kékesi, Attila, 2006)
Duration: 01:18:00 A young man and a girl on Muzeum boulevard in Budapest, shoulder to shoulder, looking directly into the camera. The above image appeared on the inner front page of the 30 October 1956 issue of Paris Match. 45 years after the photo was taken, historian Eszter Balázs and journalist Phil Casoar set up a journey to trace the young couple and find out who they were, whether they survived the revolution, and if yes, where they live. The film follows them in their quest. Since there was more information available about the girl, she is the one whose path the filmmakers trace. It turns out that the Paris Match image of the revolutionary girl is not simply a record of a moment in her life, but actually the publication of the photo in the Western press influenced her entire life. She had to flee Hungary partly because of that photo. On the other hand, that photo made her one of the best-known immigrants. She tried to become identical with the image of that photograph, therefore in the eyes of her acquaintances she remained the Hero of the Revolution. In the film, witnesses of her life, as well as the photographer tell their stories.